Low-velocity impact of multilayer sandwich beams with metal foam cores: Analytical, experimental, and numerical investigations. (March 2020) - Zhang, Jianxun; Qin, Qinghua; Chen, Shangjun; Yang, Yan; Ye, Yang; Xiang, Chunping; Wang, TJ
This paper uses the analytical, experimental and numerical methods to investigate the low-velocity impact response of fully clamped multilayer sandwich beams with metal foam cores struck by a heavy mass. Using the quasi-static method, analytical solutions for dynamic response of the fully clamped multilayer sandwich beams are derived including the interaction between bending and stretching induced by large deflections. Effects of local denting and core strength on the overall bending are considered. The low-velocity impact experiments and numerical calculations are carried out to validate the analytical model. The present analytical model captures experimental and numerical results reasonably. It is shown that the energy absorption of multilayer sandwich beams increases with decrease of multilayer factor and increase of the core strength.